Perlindungan Pelaku Terorisme dari Segi Hak Asasi Manusia, dan Perlindungan Korban Terorisme Berdasarkan Undang-Undang No. 5 Tahun 2018 - Janter Panjaitan; SyahputraAditya K S; Elyassin Firdaus; Prastian Nur Huda (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The handling of terrorism crimes in Indonesia requires a balance between safeguarding the rights of perpetrators as individuals entitled to human rights and fulfilling the rights of victims affected by such acts of violence. This study aims to evaluate how human rights protections for terrorism suspects are upheld during legal proceedings, as well as how the state strives to protect and rehabilitate victims of terrorism under Law No. 5 of 2018 on the Eradication of Criminal Acts of Terrorism. Using a normative juridical approach, this research analyzes a case study based on the North Jakarta District Court’s Decision No. 1580/Pid.Sus.Terrorism/2020/PN.Jkt.Utr. The findings indicate that terrorism suspects are granted fair legal treatment, including the right to defense, a fair trial, and protection from torture, in accordance with the principle of non-derogable rights under international human rights law. On the other hand, Law No. 5 of 2018 establishes a clearer and more comprehensive legal framework to ensure victims' rights, including rehabilitation, compensation, and restitution. However, the implementation of victim protections still faces various technical and administrative challenges. This study recommends strengthening mechanisms for victim protection and enhancing legal enforcers' awareness of human rights principles in handling terrorism cases.